Comparative kinematic analysis of softball swing in female and male players - Orescanin, L.; Hraski, Z. (World Congress of Performance Analysis of Sport XII, 2018)
The purpose of this study was to compare softball swing performance of two athletes, male and female, and comparison of the achieved results with results from previous similar researches. Both players were members of the Croatian national senior team, and hade been playing softball for a long time. Each player hit 24 balls (two sets of 12 balls) after a standard warm-up. Three video cameras, operating at 60 frames per second, were positioned to provide 3D analysis and used for recording the performances. The best hit of each player, chosen by the expert team of coaches, players and umpires, was subjected to further analysis. Although the functioning of kinetic chain was efficient in both analyzed hits, significant differences occurred in the variables of elbow angles. In the female swing a much larger angle was registered than in the male one, which led to a slower elbow extension speed. The female player opened her shoulder prematurely, and pushed the knob too much off, instead of staying inside the ball trajectory and keeping the knob close to her body. Players often mistakenly go around the ball, instead staying in and then push properly through the extension phase. Speed of elbow extension is very important for the ball trajectory, as much as the knob path.